Association of Central Obesity and Hypertension in an Urban Area - Chandrayani Simanjorang; Diva Anita Churiana Sudrajat; Ulya Qoulan Karima (Jurnal Keperawatan Indonesia, 2026)
Hypertension is one of the non-communicable diseases in Indonesia that is closely related to obesity. Therefore, this study aimed to determine the association between central obesity and hypertension in a cohort study group in Bogor City from 2011 to 2021. A retrospective cohort study design was employed, with multivariate Cox regression analysis performed using secondary data from the Risk Factors for Non-Communicable Diseases (FRPTM) Cohort Study. Among 3,586 samples, 879 incident cases of hypertension were observed by the end of follow-up, accounting for 24.5% of the at-risk population. The incidence rate of hypertension was 28 cases per 1000 people per year, with a cumulative incidence rate of 25%. Multivariate analysis found that people with central obesity (RR: 1.415; 1.181-1.694) had a higher risk of developing hypertension. Other covariates were present, including age (p = 0.000), obesity (p = 0.000), light smoking (p = 0.000), moderate smoking (p = 0.011), and heavy smoking (p = 0.035). The control of central obesity through routine waist circumference screening in primary health care can serve as an important opportunity to prevent hypertension.